2012
DOI: 10.1186/1532-429x-14-15
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance by non contrast T1-mapping allows assessment of severity of injury in acute myocardial infarction

Abstract: BackgroundCurrent cardiovascular magnetic resonance (CMR) methods, such as late gadolinium enhancement (LGE) and oedema imaging (T2W) used to depict myocardial ischemia, have limitations. Novel quantitative T1-mapping techniques have the potential to further characterize the components of ischemic injury. In patients with myocardial infarction (MI) we sought to investigate whether state-of the art pre-contrast T1-mapping (1) detects acute myocardial injury, (2) allows for quantification of the severity of dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
227
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(250 citation statements)
references
References 37 publications
12
227
5
6
Order By: Relevance
“…The increased LV mass 24 is presumably a reflection of the significant myocardial edema seen in the myocardium during the acute stage, previously reported by us and others 7,21,25 . There is extensive evidence that pre-contrast T1 mapping is reflective of edema, previously provided from our group 26 and by others [27][28][29] . Here we replicate our previous findings 7 showing that LV edema subsides in the previously well contracting segments.…”
Section: Current Results In Context Of Previous Literaturementioning
confidence: 72%
“…The increased LV mass 24 is presumably a reflection of the significant myocardial edema seen in the myocardium during the acute stage, previously reported by us and others 7,21,25 . There is extensive evidence that pre-contrast T1 mapping is reflective of edema, previously provided from our group 26 and by others [27][28][29] . Here we replicate our previous findings 7 showing that LV edema subsides in the previously well contracting segments.…”
Section: Current Results In Context Of Previous Literaturementioning
confidence: 72%
“…45 There are several studies that showed that T1-mapping is useful in identifying more diffuse forms of fibrosis in the remote myocardium and the peri-infarct area (the acquisition time is faster and the spatial resolution is better). 46,47 The notion of peri-infarct zone ("gray zone") was introduced by Schmidt et al The quantification of the peri-infarcted zone can be made by tracing the endo-and epicardial margins in the short-axis sequence and the hypersignal region. 41 The infarct nucleus is defined as the region from the myocardium with a signal intensity higher than 50%.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…LGE+ segments were used as the oedema-positive test state, as previously described, [3] and normal segments from healthy volunteers were used as the oedemanegative test state. All T1 map and T2W-SPAIR segments were categorised as LGE+ or LGE-, and were only included if they were artefact-free in both T1 maps and T2W-SPAIR images.…”
Section: T1 Mapping Versus T2w-spair: Performance For Detecting At-rimentioning
confidence: 99%
“…Quantitative T1 mapping has recently emerged as a powerful tool for myocardial tissue characterisation, [1] and previous work has already illustrated its utility for delineating myocardial oedema in acute myocardial infarction (AMI), [2,3] and acute stress-induced cardiomyopathy patients. [4,5] We have seen that, in the first 24 hours after acute myocardial injury, native T1 mapping assessment of oedema appears to be at least as good as that of T2-weighted (T2W) short tau inversion recovery imaging, [3] which is the current standard for oedema assessment with cardiovascular magnetic resonance (CMR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation